2019
DOI: 10.3389/fpsyg.2019.02756
|View full text |Cite
|
Sign up to set email alerts
|

Semantic-Pragmatic Impairment in the Narratives of Children With Autism Spectrum Disorders

Abstract: Narrative impairments are common in autism spectrum disorders (ASDs). The Autism Diagnostic Observation Schedule (ADOS) battery includes a story-telling activity using a picture book called Tuesday. The current study aimed to identify differences between children with ASD and children with typical development (TD) on the production of Tuesday narratives, with a special focus on semantic-pragmatic aspects. Participants were 48 cognitively-able boys, in the age range of 4;10-7;0 years. Twenty-four participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…A recent review of electrophysiological studies of speech processing in ASD (Key & D'Ambrose Slaboch, 2021) suggests that abnormalities are more prominent with increasing stimulus and task complexity and the authors propose that most of the speech processing deficits observed are due to lack of social interest rather than impairments at basic auditory and speech processing levels. Support for this assertion comes from past research showing that individuals with ASD have difficulty with language processing at narrative levels (Coderre et al, 2018; Jolliffe & Baron‐Cohen, 2000; Kenan et al, 2019; Vermeulen, 2015). The story used in our study represents a complex naturalistic narrative with socially relevant content.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of electrophysiological studies of speech processing in ASD (Key & D'Ambrose Slaboch, 2021) suggests that abnormalities are more prominent with increasing stimulus and task complexity and the authors propose that most of the speech processing deficits observed are due to lack of social interest rather than impairments at basic auditory and speech processing levels. Support for this assertion comes from past research showing that individuals with ASD have difficulty with language processing at narrative levels (Coderre et al, 2018; Jolliffe & Baron‐Cohen, 2000; Kenan et al, 2019; Vermeulen, 2015). The story used in our study represents a complex naturalistic narrative with socially relevant content.…”
Section: Discussionmentioning
confidence: 99%
“…Their speech is characterised by low levels of language abstraction, with few words related to feelings (Chojnicka & Wawer, 2020) and production of descriptive or action sequences (Westerveld & Roberts, 2017), with reduced references to semantic-pragmatic elements, as basic story details (e.g. characters, settings, actions) and complex concepts, reflected in the story's central ideas (Kenan et al, 2019). Later, in school age, the narratives of autistic children remain syntactically less complex, contain more ambiguous pronouns and include fewer story grammar elements than those of TD peers (Banney et al, 2015).…”
Section: Comparison Between Semantic Skills Of Autistic Children and ...mentioning
confidence: 99%
“…After watching each clip, the participants were asked to write in brief what they thought the scene was about and what had particularly captured their attention. These were used to formulate 'central ideas' (similar to the study by Kenan et al, 2019) to capture what was typically considered relevant for each scene. The sub-study participants were also provided with seven multiple-choices depicting pragmatic elements of each clip and asked to rate them from one to three to indicate which of the alternatives they thought described each video the best.…”
Section: Coding Schemementioning
confidence: 99%